Priority Needs for Developing Risk Management Based on the Four Iddhipda Principles of School Administrators Under the Khon Kaen Primary Educational Service Area Office 2 - Klangwong, Jongjit; Kangpheng, Samrit; Chotivungso, PhrakhrupaladBoonchuay (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aimed (1) to study the current condition of risk management based on the Four Iddhipada principles of school administrators under the Khon Kaen Primary Educational Service Area Office 2, and (2) to propose guidelines for improving such risk management. A mixed-methods approach was employed, using both quantitative and qualitative research methods. The instruments used were a questionnaire with a Cronbach’s alpha reliability of 0.986 and an interview form. The sample consisted of 419 school directors and teachers, while the key informants were nine individuals selected through purposive sampling. The research results were as follows: 1. The needs for developing risk management based on the Four Iddhipada principles were found to be at a significant level requiring improvement. This was determined through a comparative analysis between the current state, which was at a moderate level, and the desirable state, which was at a high level across all aspects, revealing a clear development gap. When prioritizing the needs, it was found that compliance with rules and regulations was the most urgently required area for development, followed by operational aspects, financial aspects, and strategic aspects, respectively. 2. The development guidelines are as follows: (1) Regulatory compliance: administrators should serve as good role models, uphold honesty and transparency, encourage voluntary compliance, and maintain fairness in supervision; (2) Operations: promote participation, provide opportunities for expressing opinions, recognize exemplary performers, and develop skills to enhance efficiency; (3) Finance: manage budgets with transparency and accountability, prepare regular reports, use online accounting systems, and allocate budgets appropriately; (4) Strategy: implement plans systematically, communicate the vision clearly to ensure shared understanding, and monitor and adjust plans according to context to strengthen sustainable risk management in schools.